2018
DOI: 10.1097/brs.0000000000000608
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postoperative Infections After Single-Level Lumbar Fusion Surgery

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 37 publications
3
36
0
1
Order By: Relevance
“…[34][35][36][37][38][39][40] Regarding surgical complications specifically, multiple studies have demonstrated an association between obesity and the incidence of surgical site infections. 35,38,39,41,42 The increased risk for surgical site infections in obese patients has been attributed to the increased risk of fat necrosis in this population, serving as a nidus for infection. Additionally, when utilizing a posterior approach, obese patients can create a more technically demanding procedure due to limited patient mobility and increased difficulty during surgical exposure.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40] Regarding surgical complications specifically, multiple studies have demonstrated an association between obesity and the incidence of surgical site infections. 35,38,39,41,42 The increased risk for surgical site infections in obese patients has been attributed to the increased risk of fat necrosis in this population, serving as a nidus for infection. Additionally, when utilizing a posterior approach, obese patients can create a more technically demanding procedure due to limited patient mobility and increased difficulty during surgical exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple risk factors have been identified as predictors of SSI including greater than one liter of intraoperative blood loss, operative time greater than 3 hours, inpatient stay greater than 1 week prior to index operation, and preoperative patient characteristics including smoking, alcohol abuse, malnutrition, diabetes and long-term steroid use [25]. The USA National Healthcare Safety Network reported a mean SSI rate of 0.7% to 4.2% for spinal fusions and 0.7% to 2.3% for laminectomies [6].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 One of the few studies examining this topic was conducted by Lim et al 4 These authors found that the incidence of pneumonia after one-level lumbar fusion procedures was 0.6%. A second study reported that the in-hospital incidence of pneumonia after lumbar fusion procedures was 1.05%.…”
mentioning
confidence: 99%